2014
DOI: 10.1007/s12013-014-0180-5
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between p21 Gene rs1059234 Polymorphisms and Risk of Endometrial Cancer Among Han Women in Northeast China

Abstract: Objective of the study is to find the association between p21 rs1059234 polymorphisms and endometrial cancer in Han women from Northeast China. Genotyping of rs1059234 in the p21 gene was performed by sequencing and PCR-restriction fragment length polymorphism (PCR-RFLP) of peripheral blood samples in 263 endometrial cancer patients (case group) and 315 healthy subjects (control group). C allele frequency of rs1059234 was significantly increased in patients of the case group when compared with that in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…So far, the functional role of the p21 rs1059234 variant has not yet to be well interpreted, several published clinic studies reported this variant was at increased risk of developing various cancer (Li et al, 2005;Lei et al, 2010;Liu et al, 2013). However, a number of published clinic studies reported this variant was not involved in the risk of cancer (Wu et al, 2006;Zheng et al, 2014;Yin et al, 2015). These conflicting studies based their conclusions on a small number of samples, so a metaanalysis of all available studies will help to establish a more convincing result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the functional role of the p21 rs1059234 variant has not yet to be well interpreted, several published clinic studies reported this variant was at increased risk of developing various cancer (Li et al, 2005;Lei et al, 2010;Liu et al, 2013). However, a number of published clinic studies reported this variant was not involved in the risk of cancer (Wu et al, 2006;Zheng et al, 2014;Yin et al, 2015). These conflicting studies based their conclusions on a small number of samples, so a metaanalysis of all available studies will help to establish a more convincing result.…”
Section: Discussionmentioning
confidence: 99%
“…Yong-Sheng Huang, Qian-Qian Fan, Chuang Li, Meng Nie, Hong-Yang Quan, Lin Wang* of studies have reported the role of p21 rs1059234 polymorphism in cancer risk (Li et al, 2005;Lei et al, 2010), but the results remain conflicting (Sivonova et al, 2013;Yin et al, 2015), partially because of the relatively small sample size in each of the published studies. Therefore, here we performed a large scale meta-analysis of all the published studies to derive a more precise quantitative assessment of the association between p21 rs1059234 polymorphism and the cancer risk.…”
Section: Quantitative Assessment the Relationship Between P21 Rs1059234 Polymorphism And Cancer Riskmentioning
confidence: 99%
“…Forty-four publications were further removed, among which 25 publications were unrelated with p21 3′ UTR rs1059234 polymorphism and cancer risk, 9 were meta-analysis, 4 were not case-control studies, 2 were reviews, 2 were letter to editor, 1 used cancer patients as controls and last one was overlapped with others. After the removal of all studies that didn’t meet our criteria, a total of 11 eligible studies were finally included in our meta-analysis 7 19 20 21 22 23 24 25 26 27 28 . Table 1 listed the main characteristics of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a number of molecular epidemiological studies have been done to evaluate the association between p21 3′ UTR rs1059234 polymorphism and different types of cancer risk in diverse populations 7 19 20 21 22 23 24 25 26 27 28 . However, the results were inconsistent or even contradictory, partially because of the possible small effect of the polymorphism on cancer risk and the relatively small sample size in each of published study.…”
mentioning
confidence: 99%